Clinicopathologic significance of nuclear HER4 and phospho-YAP(S127) in human breast cancers and matching brain metastases. (July 2020) - Kalita-de Croft, Priyakshi; Lim, Malcolm; Chittoory, Haarika; de Luca, Xavier M.; Kutasovic, Jamie R.; Day, Bryan W.; Al-Ejeh, Fares; Simpson, Peter T.; McCart Reed, Amy E.; Lakhani, Sunil R.; Saunus, Jodi M.
Background: Human epidermal growth factor receptor-4 (HER4) and yes-associated protein-1 (YAP) are candidate therapeutic targets in oncology. YAP's transcriptional coactivation function is modulated by the HER4 intracellular domain (HER4-ICD) in vitro, but the clinical relevance of this has not been established. This study investigated the potential for targeting the HER4-YAP pathway in brain metastatic breast cancer. Methods: We performed immuno-phenotypic profiling of pathway markers in a consecutive breast cancer series with 25 years of clinical follow up ( n  = 371), and patient-matched breast and metastatic brain tumours ( n  = 91; 30 pairs). Results: Membrane localisation of phospho-HER4 [pHER4(Y 1162 )] was infrequent in primary breast cancer, but very frequent in brain metastases (5.9% versus 75% positive), where it was usually co-expressed with pHER3(Y 1289 ) ( p  < 0.05). The presence of YAP in tumour cell nuclei was associated directly with nuclear pERK5(T 218 /Y 210 ) ( p  = 0.003). However, relationships with disease-specific survival depended on oestrogen receptor (ER) status. Nuclear pYAP(S 127 ) was associated with smaller, good prognostic ER+ breast tumours (log-rank hazard-ratio 0.53; p  = 9.6E −03 ), but larger, poor prognostic triple-negative cancers (log-rank hazard-ratio 2.78; p  = 1.7E −02 ), particularly when co-expressed with nuclear HER4-ICD ( p  = 0.02). This phenotype was associated with stemness and mitotic instability markers (vimentin, SOX9, ID1, SPAG5, TTK, geminin; p  < 0.05). YAP expression in brain metastases was higher than matched primary tumours; specifically, nuclear pYAP(S 127 ) in ER-negative cases ( p  < 0.05). Nuclear YAP was detected in ~70% of ER-negative, HER4-activated brain metastases. Discussion: Our findings suggest that the canonical-mechanism where Hippo pathway-mediated phosphorylation of YAP ostensibly excludes it from the nucleus is dysfunctional in breast cancer. The data are consistent with pYAP(S 127 ) having independent transcriptional functions, which may include transducing neuregulin signals in brain metastases. Consistent with mechanistic studies implicating it as an ER co-factor, nuclear pYAP(S 127 ) associations with breast cancer clinical outcomes were dependent on ER status. Conclusion: Preclinical studies investigating HER4 and nuclear YAP combination therapy strategies are warranted.